A Research on the Design of Intangible Cultural Heritage to Develop Cultural Creative Products : A Case Study of "Ninigou" Clay Statuette in Huaiyang City - Li , Zhaoyu; Rohitasuk, Sitthidham; Phuyuthanon, I-na (Journal of Roi Kaensarn Academi, 2023)
In an endeavor to bridge the gap between cultural heritage and modern design, this study undertook an exploration into a methodical approach for the design of cultural and creative products, with a specific focus on the Ninigou, an element of intangible cultural heritage. The aim of this study was to propose a methodological approach for cultural and creative products design. The research established a theoretical framework based on related literature and research on intangible cultural heritage and cultural and creative product design. A variety of research methods were used, targeting different participant groups such as intangible cultural heritage inheritors, practitioners of Ninigou, villagers no longer engaged in Ninigou production, Ninigou sellers, and tourists. Data was collected through in-depth and general interviews, as well as a questionnaire survey, yielding insights on the state of Ninigou intangible cultural heritage, perspectives of practitioners, and tourist attitudes towards cultural and creative products. The research findings revealed the historical and cultural significance of Ninigou, its tangible and intangible characteristics, consumer preferences, and the importance and potential of narrative design in cultural and creative product design and development. In order to develop cultural and creative products design, it was necessary to focus on the four-step narrative design process. The steps include cultural selection, thematic establishment, narrative plot setting, and product narrative design.